IEC 61850-Based Smart Substations : Principles, Testing, Operation and Maintenance - Yuan, Yubo, editor 649140; Yang, Yi, editor 649141; ScienceDirect (Online service) 7722 (London : Academic Press, 2019)
IEC 61850-Based Smart Substations: Principles, Testing, Operation and Maintenance systematically presents principles, testing approaches, and the operation and maintenance technologies of such substations from the perspective of real-world application. The book consists of chapters that cover a review of IEC 61850 based smart substations, substation configuration technology, principles and testing technologies for the smart substation, process bus, substation level, time setting and synchronization, and cybersecurity. It gives detailed information on testing processes and approaches, operation and maintenance technologies, and insights gained through practical experience. As IEC 61850 based smart substations have played a significant role in smart grids, realizing information sharing and device interoperation, this book provides a timely resource on the topics at hand.